2016
DOI: 10.1176/appi.ps.201500281
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Suicidal Thoughts: A Survey of Personal Experience

Abstract: Objective Describe use of services and self-care strategies by people experiencing suicidal thoughts. Methods Constituents of the Depression and Bipolar Support Alliance (n=611) completed an anonymous online survey regarding experience of suicidal ideation and use of a range of clinical services, community supports, and self-care strategies. Results Mental health providers were the most frequently used and the most favorably rated sources of support. Peer supports were less frequently used, bu also favorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…However, some veterans felt they played games excessively or were addicted, and reported that gaming affected relationships, finances or time management. Thematic analysis clarified how our sample’s use of video games corresponds to known areas of mental health recovery and suicide prevention (Bryan, 2016; Bush et al, 2015; Deegan, 2005; Garland et al, 2015; MacDonald-Wilson et al, 2013; National Academies of Sciences, 2016; Shand et al, 2015; Simon et al, 2016; Struszczyk et al, 2017; Villaggi et al, 2015; Whitley and Drake, 2010), as illustrated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, some veterans felt they played games excessively or were addicted, and reported that gaming affected relationships, finances or time management. Thematic analysis clarified how our sample’s use of video games corresponds to known areas of mental health recovery and suicide prevention (Bryan, 2016; Bush et al, 2015; Deegan, 2005; Garland et al, 2015; MacDonald-Wilson et al, 2013; National Academies of Sciences, 2016; Shand et al, 2015; Simon et al, 2016; Struszczyk et al, 2017; Villaggi et al, 2015; Whitley and Drake, 2010), as illustrated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding suicide-specific coping, Simon et al ( 47 ) asked participants in an online survey which adaptive (e.g., distraction, positive self-talk) and maladaptive (e.g., alcohol and substance use) coping strategies they apply when experiencing suicidal thoughts. They found, for example, that almost 90% of participants used distraction, a method they experienced as moderately useful.…”
Section: New Directions Of Conceptualizing Suicidality: the Dual-syst...mentioning
confidence: 99%
“…To increase adherence to treatment, it seems particularly important to consider the patients' perspective when developing interventions. This is also advocated by health-care agendas (Barr et al, 2014), especially as Simon, Specht, and Doederlein (2016) revealed the paradox that whereas the large majority of people who experienced suicide ideations agreed that forced treatment is sometimes required, more than half of the sample was unwilling to speak with a professional about their suicidality. To conclude, there is a lack of depression-specific group therapy approaches that address suicidality directly.…”
Section: Introductionmentioning
confidence: 99%